Accounting treatments of biological assets and agricultural products - Marrufo Garcia, Rubén Darío (2021)
Fil: Marrufo Garcia, Rubén Darío. Dr. Rafael Belloso Chacin University. Faculty of Administrative Sciences; Venezuela.